BLUE OCEAN STRATEGY : SEBUAH UPAYA KELUAR DARI PERSAINGAN - Nina Septina (Center for Economic Studies Universitas Katolik Parahyangan, 2007)
A competition in business is like a never ending war. Market competitions arc getting tighter in every single aspect. Many efforts had been done to win the battle. This one called Red Ocean Strategy, where every player tries hard to compete and beat the competition. The winner still has to survive their position in the existing market, to keep away from being shadowed by the competitor. The term Blue Ocean sounds new, but its existence is not. lt is a feature of business life, past and present. value innovation is the cornerstone of blue ocean strategy. The core of this paper is about the analytical tools and frameworks of blue ocean strategy which are The Strategy Canvas, The Four Actions Framework and The Eliminate-Reduce-Rai*-Create Grid.